Palladium-Catalyzed Synthesis of Mono- and Diphosphorylated 1,10-Phenanthrolines - Mitrofanov, Alexandre; Bessmertnykh Lemeune, Alla; Stern, Christine; Guilard, Roger; Gulyukina, Nataliya; Beletskaya, Irina (Synthesis, 2012)
A general protocol for the coupling of mono- and dihalo-1,10-phenanthrolines with diethyl phosphite is reported. This reaction proceeds smoothly in the presence of a Pd(OAc)2/dppf catalytic system and triethylamine as a base.
Keywords: catalysis; cross-coupling; palladium; heterocycles; phosphorylation